1989
DOI: 10.1161/01.str.20.7.876
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic infarct of the brain without a reopening of the occluded arteries in cardioembolic stroke.

Abstract: We examined the brains of 14 patients (four men and 10 women, mean age 68.9 years) who died from brain herniation after cardioembolic stroke with persistent occlusion of the internal carotid-middle cerebral arterial axis. Our examination showed hemorrhagic infarct in seven patients and pale infarct in the other seven, contradicting the commonly proposed pathophysiologic mechanism for the development of hemorrhagic infarct that the opening of previously occluded vessels makes an infarct hemorrhagic. Analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 16 publications
2
37
0
1
Order By: Relevance
“…19 Occasionally, delayed hemorrhage occurs without reperfusion, and in these cases, the source of the hemorrhage is postulated to be collateral circulation to the damaged area. 20 An interesting association also occurs between time to artery reopening and presence of HT in our series. Most patients with early HI recanalized within 12 hours, but all patients who developed late HI had an absence of early spontaneous recanalization.…”
Section: Discussionsupporting
confidence: 68%
“…19 Occasionally, delayed hemorrhage occurs without reperfusion, and in these cases, the source of the hemorrhage is postulated to be collateral circulation to the damaged area. 20 An interesting association also occurs between time to artery reopening and presence of HT in our series. Most patients with early HI recanalized within 12 hours, but all patients who developed late HI had an absence of early spontaneous recanalization.…”
Section: Discussionsupporting
confidence: 68%
“…Brain edema and hemorrhagic transformation are key factors to link acute high BP and poor outcomes. 4,[17][18][19] The spontaneous decline in BP during the initial hours sometimes reflects the recanalization of occluded cerebral arteries, which often results in favorable outcomes. 20,21 Mental stress of hospital admission contributes to elevated BP 11 ; release from the stress can lower BP and possibly improve clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…4 It has been suggested that hemorrhagic infarction is a result of multifocal red blood cell extravasation, whereas parenchymal hematoma is the a result of a single bleeding site in the blood vessel damaged by ischemia and reperfusion. 51 Reperfusion of injured brain tissue, related to recanalization of the affected artery, 52 provides the impetus for the development of hemorrhagic transformation. Recanalization of the affected artery, however, is not the only determinant of the risk of hemorrhagic transformation, which can also occur with persistent occlusion, as noted in autopsy and imaging studies.…”
Section: Pathophysiology Of Alteplase-related Hemorrhagic Transformationmentioning
confidence: 99%
“…Recanalization of the affected artery, however, is not the only determinant of the risk of hemorrhagic transformation, which can also occur with persistent occlusion, as noted in autopsy and imaging studies. 52,53 Reperfusion injury may be exacerbated by or lead to elevated blood pressure. 54,55 In addition, postthrombolytic hemorrhage can occur in areas remote from the infarcted tissue, 56 lending support to the notion that thrombolytics can contribute to hemorrhage by mechanisms other than reperfusion.…”
Section: Pathophysiology Of Alteplase-related Hemorrhagic Transformationmentioning
confidence: 99%